(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present paper aims to examine how industrial sites can be more easily 3D scanned by integrating a self-moving autonomous robotic system and a large scale scanning technique. A case study is developed where an Unitree Go 1 Edu quadruped robot and a Trimble X7 3D laser scanning system are combined to illustrate the successful integration. For the full integration of the 3D scanner and the robot, several components are designed, using CAD software, and produced via Rapid Prototyping technologies. In the case study, different 3D scanning regimes are also tested. The case study showcases how the industrial 3D scanning process can be aided and potential ideas for the integration of 3D scanning technologies with quadruped robots are further discussed in the paper.